Protocolo de acolhimento das mulheres em situação de violência doméstica e familiar: um olhar translacional aos casos de violência institucional no Estado do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation aims to analyze the effects of institutional violence on the lives of women in situations of domestic and family violence. The research stems from the question of how the State, through its institutions, can become an agent of oppression instead of offering protection, and what are the consequences of this in the fight and prevention of domestic and/or family violence? Here, institutional violence is understood as violence practiced by public servants, whose inefficient or aggressive actions can worsen the suffering of women seeking help, violating their rights instead of protecting them. The relevance of the topic is evidenced by the high rates of domestic and/or family violence in Brazil. Therefore, the study investigates how this institutional violence manifests and affects the process of addressing domestic and/or family violence, with a specific focus on Women's Police Stations (DEAMs), particularly in the city of Ponta Grossa/Paraná. The dissertation proposes that, for the fight against domestic and/or family violence to be effective, it is also necessary to combat the institutional violence imposed on women. The State, by failing to provide proper support and protection, ends up contributing to the increase in cases of violence, perpetuating the cycle of violence and the lack of safety in these women's lives. In this context, the research suggests that a change in the approach to women in situations of violence, through the creation of a Reception/Support Protocol for DEAMs, could represent a significant innovation. Based on principles of Translational Research applied to Law, the study combines theoretical knowledge and practical experience, seeking ways to improve the Justice System and ensure women's rights. To this end, it employs a methodological approach that involves literature review, documentary analysis of laws, legislative projects, and data collection from women served by the DEAMs and the Maria da Penha Center at the State University of Ponta Grossa - NUMAPE/UEPG. Finally, the dissertation's product is the development of a Reception/Support Protocol aimed at humanizing and making the service at Paraná's DEAMs more efficient. The protocol seeks to create an environment where women in situations of violence do not feel doubly victimized when seeking help, promoting an integral service that effectively protects their rights.
Keywords: Violência Institucional; Violência doméstica e/ou familiar; Lei Maria da Penha; Delegacia Especializada em Atendimento à Mulher; Núcleo Maria da Penha; Revitimização; Institutional Violence; Domestic and/or Family Violence; Maria da Penha Law; Women's Police Station; Maria da Penha Center; Revictimization; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO